Population Distribution of Vibrational Levels of the 2\(^1Π\) State of NaLi - Dung, Nguyen Tien (Communications in Physics, 2017)
We studied population distribution of vibrational levels for the 2\(^1Π\) of NaLi molecule from \(v’=0\) to \(v’=16\). The population of the levels was calculated numerically by solving the radial Schrodinger equation with an experimental potential extrapolated to the dissociation limit via a long range potential. We found that, for each highly excited level its population distribution is favorable around the right turning-point. The results provide important information for choosing convenient experimental parameters and explaining dynamical processes in the molecule